2019
DOI: 10.1093/jee/toz218
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Bacterial Isolates on Adults of Zaprionus indianus (Diptera: Drosophilidae) and Parasitoids Trichopria anastrephae (Hymenoptera: Diapriidae) and Pachycrepoideus vindemmiae (Hymenoptera: Pteromalidae)

Abstract: Bacillus thuringiensis (Berliner) has demonstrated potential use in insect pest management. We evaluated the toxicity and sublethal effects of formulations of toxic baits composed of bacterial isolates (Bt) B. thuringiensis var. oswaldo cruzi (Bto), B. thuringiensis var. israelensis (Bti), B. thuringiensis var. kurstaki (Btk), and B. circulars (Bc) in combination with three food attractants 50% grape juice, 7% sugar cane molasses, and 7% hydrolyzed protein on adults of Zaprionus indianus (Gupta, 1970), the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Considering that the toxin acts in the digestive system (Ben-Dov 2014), the greater the exposure to the toxin, the greater the consumption of food contaminated with the bacteria, and therefore, the greater should be the impact on the larvae metabolism (Taylor et al 2007). The susceptibility of larvae of dipteran species to B. thuringiensis isolates has been demonstrated in several studies (Aboussaid et al 2010;Molina et al 2010;Ilias et al 2013;Shishir et al 2015;Buentello-Wong et al 2015;Cossentine et al 2016;Geisler et al 2019;Martins et al 2018), however, for sciarids and some mosquitoes, such as Aedes, Culex, and Anopheles, it is known that some endotoxins are more specific and effective in control (Ben-Dov 2014). Nevertheless, they act similarly to what occurs in lepidopterans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the toxin acts in the digestive system (Ben-Dov 2014), the greater the exposure to the toxin, the greater the consumption of food contaminated with the bacteria, and therefore, the greater should be the impact on the larvae metabolism (Taylor et al 2007). The susceptibility of larvae of dipteran species to B. thuringiensis isolates has been demonstrated in several studies (Aboussaid et al 2010;Molina et al 2010;Ilias et al 2013;Shishir et al 2015;Buentello-Wong et al 2015;Cossentine et al 2016;Geisler et al 2019;Martins et al 2018), however, for sciarids and some mosquitoes, such as Aedes, Culex, and Anopheles, it is known that some endotoxins are more specific and effective in control (Ben-Dov 2014). Nevertheless, they act similarly to what occurs in lepidopterans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that several species of dipterans are susceptible to B. thuringiensis, such as Anastrepha ludens (Loew) (Toledo et al 1999;Buentello-Wong et al 2015), Bactrocera oleae (Gmelin) (Alberola et al 1999;Ilias et al 2013), Ceratitis capitata (Wiedemann) (Aboussaid et al 2010), Bactrocera cucurbitae (Shishir et al 2015) and Anastrepha fraterculus (Wiedemann 1830) (Diptera: Tephritidae) (Martins et al 2018), Drosophila suzukii (Matsumura) (Cossentine et al 2016), Zaprionus indianus (Diptera: Drosophilidae) (Geisler et al 2019), Bradysia sp nr. coprophila (Cloyd and Dickinson 2006) and Bradysia difformis (Wang et al 2020).…”
Section: Title Of the Article With Up To 35 Words: Should Mention The...mentioning
confidence: 99%
“…(Marchiori et al, 2003, Marchiori and Silva, 2003, Silva et al, 2004. Bacterial isolates are considered promising for the formulation of toxic baits (Geisler et al, 2019). Epsky et al, 2014Epsky et al, , 2015Renkema et al, 2018), as well as different traps (Pasini and Link, 2011;Renkema et al, 2018;Lasa et al, 2020).…”
Section: Additional Potential Risk Reduction Optionsmentioning
confidence: 99%
“…Various hymenopteran parasitoids have been documented parasitising Z. indianus in Brazil, though with low levels of parasitisation (2–4%) (Marchiori et al., 2003, Marchiori and Silva, 2003, Silva et al., 2004). Bacterial isolates are considered promising for the formulation of toxic baits (Geisler et al., 2019).…”
Section: Pest Categorisationmentioning
confidence: 99%